2009
DOI: 10.1111/j.1399-6576.2008.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

The I‐gel®, a single‐use supraglottic airway device with a non‐inflatable cuff and an esophageal vent: an observational study in children

Abstract: Because the I-gel has a very good insertion success rate and very few complications, it seems to be an efficient and safe device for pediatric airway management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 14 publications
11
90
3
3
Order By: Relevance
“…The median leak pressure ranged between 20 and 27 cmH 2 O. The study by Beylacq et al [21] used only the size-3 i-gel in children. This has been included in the table for completeness but was not used in further analysis as our inclusion criterion was use of i-gel sizes 1-2.5.…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 99%
See 1 more Smart Citation
“…The median leak pressure ranged between 20 and 27 cmH 2 O. The study by Beylacq et al [21] used only the size-3 i-gel in children. This has been included in the table for completeness but was not used in further analysis as our inclusion criterion was use of i-gel sizes 1-2.5.…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 99%
“…Beringer et al [32] Unclear* Low Low Low Hughes et al [19] Unclear* Low Low Low Abukawa et al [23] Unclear* Low Low Low Gil et al [31] Unclear* Low Low Low Rylov et al [20] Low Low Low Low Foucher-Lezla et al [29] Low Low Low Low Franksen et al [30] Low Low Low Low Beylacq et al [21] Low Low Low Low * Decision to use i-gel or conventional supraglottic device left to discretion of senior anaesthetist so selection bias is possible. Das et al [7,8] the authors compared the i-gel with two other airway devices and the results have been separated for ease of comparison.…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 99%
“…At least one study has demonstrated a shallow learning curve before attainment of high success rates with the i-gel TM (ref. 16 ). The effective airway time (time to connection of the breathing circuit) was shorter and the average number of insertions was slightly less in the i-gel TM group, although neither was found to be significant.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…또한 합병증 발생률(10% 이내)은 다른 SAD와 유사하거나 낮다고 평가되었다 [4]. 그러나 소아 환자에서 i-gel에 대한 기도 관리 연구는 제한적이다 [8][9][10]. Table 1에 표시하였다.…”
unclassified